Analisis Hubungan Usia dan Jenis Kelamin dengan Kejadian Otitis Media Akut - Weni Hastuti (An-Najat, 2024)
Background: One of the ear diseases that often occurs in humans is acute otitis media. Acute Otitis Media (OMA) is an acute inflammation of the middle ear that lasts less than three weeks. Risk factors for AOM include age, gender, race, immunological status, cleft palate abnormalities, environmental factors such as upper respiratory tract infections. The aim of this study was to determine the relationship between age and gender with the incidence of acute otitis media at Indriati Solo Baru Hospital in 2023. Research Method: The research design uses an analytical observational method with a retrospective approach. Measurement using an observation sheet by looking at the data in the medical record. Samples were taken using consecutive sampling, a total of 123 respondents. Results: The majority were aged 5-11 years (48.9%), the majority were male, 64 respondents (52%), and the majority suffered from acute otitis media, 73 respondents (59.3%). Conclusion: based on the results of the chi square test, it was found that the p value was 0.000 and 0.001 (p < 0.05) so that Ho was rejected and Ha was accepted, which can be concluded that there is a relationship between age and gender with the incidence of acute otitis media at Indriati Solo Baru Hospital in 2023. It is hoped that nurses can provide education about otitis media to patients.